Eksplorasi Daya Tarik Wisata Desa Seloi Malere: Studi Fenomenologi Pariwisata Berkelanjutan - Achmad, Zainal Abidin; Priambodo, Alvian Rafif; Haq, Jelita Arinal; Agustina, Zalfa Nurrahmah; Sagran, Arif Abdullah; Priyadarshini, Rossyda (Metafora: Education, Social Sciences and Humanities Journal, 2024)
Sustainable tourism is a comprehensive strategy that aims to improve the quality of life by ensuring a balanced approach in the provision, development and preservation of natural and cultural resources for future generations. This study examines the prospects for sustainable tourism in Aileu District, Timor-Leste, specifically in Seloi Malere village which consists of six hamlets rich in natural beauty and cultural heritage. Using a phenomenological approach, the study explores the experiences and perceptions of local communities regarding the opportunities and challenges associated with tourism development, focusing on important sites such as Dili Vanili and Rai Mutin. The study findings indicate that although these locations have significant natural beauty and great economic potential, they are hampered by factors such as inadequate digital promotion, lack of infrastructure and uncertainty regarding future land use. The study recommends strengthening marketing efforts through social media, improving infrastructure and developing additional facilities to attract tourists and increase local income. Active involvement of local communities, together with strong government support, is identified as essential to maximizing these opportunities and realizing sustainable tourism in the region.